Respons Pertumbuhan Rumput Mulato Terhadap Pupuk Bokashi Berdasarkan Tinggi Tanaman, Panjang Daun, Dan Jumlah Anakan - Marlia, Marlia; M, Armayani; Irwan, Muh (Faculty of Animal Husbandry, University of Mataram, 2025)
This study aims to determine the provision of bokhasi compost fertilizer from laying hens to mulato grass. To determine the significant difference in the growth of mulato grass that is given bokhasi compost fertilizer from laying hens and not given fertilizer. This study was conducted in the experimental garden of the faculty of science and technology, Muhammadiyah University of Sidenreng Rappang, Which was carried out from february to may 2025. This study used a completely randomized design (CRD), consisting of four treatments and five replications. The treatments tried were P0: Not using bokhasi manure from laying hens (control), P1: 95g Bokhasi manure/polybag. P2:135g Bokhasi manure/polybag. P3:175g Bokhasi manure/polybag. In this study, there were 4 treatments and 5 groups, resulting in 20 treatment units. The results of the diversity analysis showed that the treatment of giving chicken manure bokhasi fertilizer had a very significant effect on plant height, leaf length and number of shoots. And the best dose of chicken manure bokhasi fertilizer was 135g (P2). It was able to provide a better effect on increasing the yield of mulato grass plants.